IMPROVING TEACHER PERFORMANCE AND STUDENTS ATTAINMENT THROUGH CONTEMPORARY LEADERSHIP IN ISLAMIC FORMAL SCHOOL - Indri Indri (Universitas Muhammadiyah Surakarta, 2021)
This paper aims to find and describe the concept of teacher achievement in learning. This study uses a qualitative approach. The results showed that through constructive learning, students interpret and construct a reality based on their interactions and experiences with the environment.